Predictive Value of Tpeak – Tend Indices for Adverse Outcomes in Acquired QT Prolongation: A Meta-Analysis - Tse, Gary; Gong, Mengqi; Meng, Lei; Wong, Cheuk W.; Bazoukis, George; Chan, Matthew T. V.; Wong, Martin C. S.; Letsas, Konstantinos P.; Baranchuk, Adrian; Yan, Gan-Xin; Liu, Tong; Wu, William K. K. (Frontiers in Physiology, 2018)
Background: Acquired QT interval prolongation has been linked with malignant ventricular arrhythmias, such as torsade de pointes, in turn predisposing to sudden cardiac death. Increased dispersion of repolarization has been identified as a pro-arrhythmic factor and can be observed as longer Tpeak – Tend interval and higher Tpeak – Tend / QT ratio on the electrocardiogram. However, the values of these repolarization indices for predicting adverse outcomes in this context have not been systematically evaluated. Method: PubMed, Embase and Cochrane Library databases were searched until 14th February 2018, identifying 232 studies. Results: Five studies on acquired QT prolongation met the inclusion criteria and 308 subjects with drug-induced LQTS patients (mean age: 66 ± 18 years old; 46% male) were included in this meta-analysis. Tpeak – Tend intervals were longer (mean difference [MD]: 76 ms, standard error [SE]: 26 ms, P = 0.003; I2 = 98%) and Tpeak – Tend / QT ratios were higher (MD: 0.14, SE: 0.03, P = 0.000; I2 = 29%) in patients with torsade de pointes compared to those without these events. Conclusion: Tpeak – Tend interval and Tpeak – Tend / QT ratio were higher in patients with acquired QT prolongation suffering from torsade de pointes compared to those who did not. These repolarization indices may provide additional predictive value for identifying high-risk individuals.